Desenvolvimento de protótipo de carga fictícia monofásica para ensaio em medidor de energia elétrica - Luna, José Henrique de Melo (2018)
One of society’s main concerns today is energy efficiency. This efficiency is directly linked to the quality with which the energy measurements are performed. In this context, it is essential to use reliable energy meters. On the other hand, any measuring instrument, the result of which is used in a commercial relationship, is subject to regulation. Therefore, to comply with current regulations and to provide reliability to energy measurements, the regulations establish minimum conditions to be observed in inspections and tests of these meters. Amongst the tests, the accuracy test, which has as purpose to verify if the errors of the meter are within the maximum permissible error, stands out. To perform the accuracy test, it is necessary to have a given energy circulate through the meter under test and another reference meter, comparing the value measured by the two meters. For agility, the use of the dummy load is the preferred way of circulating energy through the meters in a controlled manner due to their versatility, reduced weight and energy savings during the test. However, this solution is still little used. In this sense, the objective of this research work is the development of a prototype of dummy load for the accuracy test of monophasic electric meters to meet the needs of Inmetro and its delegated bodies.